On the application of continuous buried periodic inclusions on the filtering of traffic vibrations: A numerical study. Issue 113 (October 2018) - Castanheira-Pinto, A.; Alves-Costa, P.; Godinho, L.; Amado-Mendes, P.
Abstract: The topic of vibrations induced by rail traffic has received a special attention from the scientific community over the last decades, which is justified by the increase of health awareness and comfort demands by the communities living nearby such infrastructures. Regarding mitigation of sound waves propagation, innovative solutions based on the phononic crystals concept have been extensively studied in recent years and their capability to attenuate wave propagation at specific frequency bands is well known. However, the extension of this concept to shield sensitive buildings from elastic waves propagation induced by traffic and by other human activities is not completely understood due to the lack of studies in this topic. Therefore, the present paper aims to give a contribution on the analysis of the vibration attenuation that can be provided by buried periodic structures when applied parallel to railway tracks. To achieve this goal, a numerical approach is followed with a 2.5D finite element method combined with perfectly matched layers (FEM-PML) model, previously developed by the authors, being applied in order to obtain a deeper understanding about the attenuation effects that can be provided by arrays of periodic buried inclusions. A step-by-step study is carried out to get an accurate insight about the phenomena involved, allowing the derivation of theoretical expressions and simplified rules that can be useful for the design of vibration mitigation solutions based on this concept. Highlights: This paper is focused on mitigation of vibrations induced by traffic. Numerical approach is followed adopting a 2.5D FEM-PML model. A step by step study is performed in order to identify the system response in the presence of periodic inclusions. Theoretical expressions are proposed for the design of vibration mitigation measure. A practical example considering a train passage was carried out.